3-Naphthyl-1-phenyl-5-(4-carboxyphenyl)-2-pyrazoline – a pyrazoline based heterocyclic dye as a fluorescent label for biomolecules containing an amino group and its evaluation using HPLC. Issue 13 (3rd March 2016) - Varghese, Beena; Al-Busafi, Saleh N.; Suliman, FakhrEldin O.; Al-Kindy, Salma M. Z.
Abstract : The use of 3-naphthyl-1-phenyl-5-(4-carboxyphenyl)-2-pyrazoline as a pre-column derivatization agent for the HPLC analysis of biomolecules containing an –NH2 group is proposed in this article. Abstract : The use of 3-naphthyl-1-phenyl-5-(4-carboxyphenyl)-2-pyrazoline as a pre-column derivatization agent for the HPLC analysis of biomolecules containing an –NH2 group is proposed in this article. The derivatization conditions to obtain quantitative reaction were optimized by considering different parameters (time, temperature, pH and reagent concentration) using seven amino acids as model analytes. The resulting derivatives were well separated on a reversed-phase column with an isocratic elution profile and detected fluorimetrically at excitation and emission wavelengths of 370 and 480 nm, respectively. The proposed method was validated for accuracy, precision, sample stability, linearity, and detection and quantification limits and were all found to be satisfactory. Through this study, we are forecasting the emergence of pyrazoline based heterocyclic dyes as organic fluorescent markers for the labelling of diagnostically important compounds, for their determination and quantification of practical interest.